Effect of ratio and temperature of pretreatment using bath sonicator on recovery of pancreatic lipase inhibitory compound of Aquilaria Malaccensis leaves extract - Adanan, Musalmah (2016)
Obesity has been one of the concerned health issues that must be countered nowadays as it can be a silent killer which lead the person to high risk of threatened-diseased. Through prior research, it has been understand that Gaharu or commonly known as agarwood of genus Aquilaria has the component that can be the inhibitor to pancreatic lipase activity which helps excess fat absorption to the body. This research focuses in determining the effects of the ratio and temperature of ultrasonication using sonicator bath to the recovery of the pancreatic lipase inhibitor from Aquilaria Malaccensis leaves extract which is a very common species of Gaharu in Malaysia. In this research the subjects have been discussed starting with the introduction to the research, literature review and methodology of the experiments conducted. Through the series of experiments, the results were obtained and discussed. The experiment was conducted to determine the effects of the solid:solvent ratio and the sonicator bath temperature on recovery of phenolics and flavonoids compounds from A.Malaccensis leaves extract. The inhibitory effects to pancreatic lipase enzyme also being determined. Both fresh and dried leaves samples were used in the experiments. The ratio that has been used were 0.5, 1.0 and 1.5:100 g/mL and the temperature of sonicator varies of 50ºC, 60ºC and 70ºC. Result shows that at temperature 60ºC, dried sample at ratio of 1.5:100 g/mL have the highest contents of phenol and flavonoids compared to the fresh samples at the same conditions. By comparing the overall results, the best temperature between the three temperature variations was at 60ºC and the best ratio is 1.0:100 g/mL of dried sample to solvent.